From Europe to North America to Asia: Overcoming the Hurdles of Interdisciplinary Multicultural Teams Through a Design-Driven Process - Münch, Fabienne (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2016)
Designing a global product is complex: variations in human factors, cultural preferences, organizational patterns and production processes impact assignment complexity from design brief to product launch. Based on a longitudinal case study, this paper examines how a design-driven process enabled a multicultural distributed project team meeting high expectations and business goals. Three factors positively impacted team performance: the design-driven process that allowed for “iterative thinking”, the use of shared visual communication tools and the reflective leadership style. The case study also suggests that a design-driven process offers a peculiar context for team members to build-up cross-cultural competences on past experiences.